Telecommunications and Must-Carry regulation in Peru: review of the signal retransmission obligation and criticism of the proposals presented - Gonzáles Cucho, José Carlos (2025)
In a context of technological advancement and diversification of audiovisual services, broadcasting in Peru faces the challenge of remaining relevant and accessible to users. Although television has shifted from an educational purpose to a commercial one, its role as a tool for informational and cultural inclusion remains essential. In this scenario, the debate over the possible implementation of a must carry-must offer regime becomes relevant. This type regulation is the obligation for television operators to include broadcasters’ signals and, in turn, for broadcasters to offer their content to the operators.In this way, the authors analyze whether this regulatory model is appropriate for the Peruvian case, taking into account its social, legal, and technical particularities. To this end, the article examines the origins of this model, comparative regulatory experiences, the current Peruvian legal framework, and the conditions of the local market. The article identifies potential effects on competition, contractual freedom, pluralism, and access to information. It concludes that imposing such obligations without solid justification may prove counterproductive, as it could affect fundamental rights and undermine the sustainability of the sector. As an alternative, the article proposes fostering a more flexible and proportionate regulatory environment that promotes access to essential content without distorting market functioning.